Multi-Laboratory Cooperation for Validating Microgrid and Smart Distribution System Approaches - Marcel Otte; Daniele Pala; Carlo Sandroni; Sebastian Rohjans; Thomas Strasser (CIRED Workshop 2018, 2018)
Distributed, renewable energy resources are one of the main driving forces for the realization of a sustainable energy supply in Europe. Their stochastic generation behaviour provides a lot of challenges which have to be managed by energy utilities and network operators. Due to the help of advanced operational concepts and intelligent automation the existing power systems are currently turned into an intelligent entity, a so-called smart grid which can cope with the dynamic behaviour of such renewables. While reaping the benefits that come along with those intelligent behaviours, it is expected that the system-level testing – besides component-level characterisation – will play a more dominant role in the whole engineering process than today. Corresponding validation and testing approaches including a suitable research infrastructure covering power and automation systems equally, are partly missing. This work tackles these issues by introducing an approach for the multilaboratory cooperation which is currently implemented in the framework of the European ERIGrid project to form a pan-European and integrated smart grid research infrastructure